ANGKA KEJADIAN DAN FAKTOR RESIKO DOMINAN TERJADINYA PRESSURE ULCER - Arry Muji Astutik, Titih Huriah (Adi Husada Nursing Journal, 2017)
Pressure ulcer adalah masalah yang harus dihadapi pasien dengan penyakit kronis, kelemahan, kelumpuhan dan bahkan ini menjadi penyakit sekunder bagi pasien yang dirawat di rumah sakit. Pressure ulcer adalah suatu kondisi di mana jaringan telah rusak akibat tekanan langsung pada kulit, dan akibat gesekan. Faktor risiko pressure ulcer terdiri dari pergerakan dan pergeseran, mobilitas, kelembaban, nutrisi, usia, merokok, dan aktivitas. Tujuan dari penelitian ini adalah untuk menganalisis tingkat pressure ulcer dan menganalisis faktor risiko yang paling berpengaruh pada pressure ulcer. Penelitian ini merupakan penelitian eksploratif deskriptif. Penelitian dilakukan di RSUD Tidar Magelang pada Stroke Unit, digunakan teknik total sampling, dengan 49 responden masuk Unit Stroke pada 20 Mei-20 April 2016. Instrumen yang digunakan dalam penelitian ini menggunakan Skala Braden. Data dianalisis dengan menggunakan program SPSS dengan tabulasi silang dan analisis regresi linier. Hasilnya menunjukkan 14,3% responden pada tingkat risiko tinggi dan 32,6% pada tingkat risiko rendah dan 53,1%. Faktor risiko yang paling berpengaruh terhadap pressure ulcer adalah persepsi sensorik, kelembaban, pergerakan dan pergeseran iagnose dengan tingkat signifikansi <0,05. Faktor risiko tukak tekanan dapat dicegah dengan memberikan teknik perawatan yang lebih baik dan pemantauan berkala terhadap pasien, sehingga kualitas perawatan pasien dan pasien di rumah sakit dapat sesuai dengan kondisi pasien. Kata kunci: pressure ulcer, faktor resiko, level resiko ABSTRACT Pressure ulcer is a problem that must be faced by patients with chronic diseases, weak condition, paralysis and even this becomes a secondary suffering for patients who are hospitalized. Pressure ulcer is a condition where tissue has been damaged as a result of direct pressure on the skin, and due to friction. Risk factors for pressure ulcers consists of movement and shifting, mobility, moisture, nutrients, age, smoking, and activity. The purpose of this study was to analyzed the level of risk pressuret ulcer and analyze the risk factors which most influence on pressure ulcers. This research was a descriptive exploratory research. The research was conducted in RSUD Tidar Magelang at the Stroke Unit, used total sampling technique, with 49 respondents who entered Stroke Unit on May 20 -20 April 2016. The instrument used in this study using a Braden Scale. Data were analyzed using SPSS program with cross tabulation and linear regression analysis. The results showed 14.3% of respondents at a high risk level and 32.6% at a low risk level and 53.1% were. The risk factors that most influence on pressure ulcer that sensory perception, moisture, nutrient movement and shifting with the level of significance <0,05. Risk factors for pressure ulcers can be prevented by providing better treatment techniques and periodic monitoring of the patient, so that the quality of patient care and the patient in the hospital can be in accordance with the patient’s condition. Keywords: pressure ulcer, risk factors, the risk level DAFTAR PUSTAKA Braden BJ, Bergstrom N . (2000). A Conceptual Schema For The Study Of The Etiology Of Pressure Sores. Rehab Nursing, 44-45. Bredesen, Ida Marie et al. (2013). The prevalence, prevention and multilevel variance of pressure ulcers in Norwegian hospitals: A cross-sectional study. International Journal of Nursing Studies , Volume 52 , Issue 1 , 149 - 156 (1992). A clinical trial of the braden scale for predicting pressure sore risk. Nurs Clin Nort Am. 22 (2) 417-428. Compher, Charlene, et al. (2007)."Obesity reduces the risk of pressure ulcers in elderly hospitalized patients." The Journals of Gerontology Series A: Biological Sciences and Medical Sciences.11: 1310-1312. Davis, Jennifer .(2011). Decubitus ulcer: risk factors, prevention and treatment. The Veterinary Nurse. 23 : 130-139. Eberlein-Gonska M, Petzold T, Helaß G, Albrecht DM, Schmitt J. The Incidence and Determinants of Decubitus Ulcers in Hospital Care: An Analysis of Routine Quality Management Data at a University Hospital. Deutsches Ärzteblatt International. 110(33-34):550-566. doi:10.3238/arztebl.(2013).0550. Lahmann, Nils A.; Tannen, Antje; Dassen, Theo dan Kottner, Jan. 2009. Friction and shear highly associated with pressure ulcers of residents in long-term care – Classification Tree Analysis (CHAID) of Braden items. Journal of Evaluation in Clinical Practice, Blackwell Ltd. ISSN 1356-1294. Ledoux WR, Shofer JB, Cowley MS, Ahroni JH, Cohen V, Boyko EJ. (2013). Diabetic foot ulcer incidence in relation to plantar pressure magnitude and measurement location. Journal of diabetes and its complications. 302-304. Man, Shiu-piu et al. (2013). Hypotension Is a Risk Factor for New Pressure Ulcer Occurrence in Older Patients After Admission to an Acute Hospital .Journal of the American Medical Directors association. Volume 14 , Issue 8 , 627.e1 - 627.e5 Page, Karen Nicola; Barker, Anna Lucia dan Kamar, Jeannette. (2010). Development and validation of a pressure ulcer risk assessment tool for acute hospital patients. The Wound Healing Society. 506-507. Rich SE, Shardell M, Hawkes WG, et al. (2011). Pressure-Redistributing Support Surface Use and Pressure Ulcer Incidence in Elderly Hip Fracture Patients. Journal of the American Geriatrics Society. 59(6):1052-1059. doi:10.1111/j.1532-5415. 03446. Sharma, Upasana, Sukhpal Kaur, and Amarjeet Singh. (2013). "Knowledge, beliefs and practices of caregivers regarding home based bedsore care in Chandigarh, North India." J Postgrad Med Edu Res.3.138-143. Sugama . (2000). New Synthetic Fiber Sheets Prevention Moisture And Heat Retention And Reduce Shear In Bedfast Patients. World Council Of Enterostmal Therapists Journal. Swanson, Melvin S., et al. (2011). "Braden subscales and their relationship to the prevalence of pressure ulcers in hospitalized obese patients." Bariatric Nursing and Surgical Patient Care. 6.1:21-23. Sving, Eva et al. Factors contributing to evidence-based pressure ulcer prevention. A cross-sectional study. International Journal of Nursing Studies. Volume 51 , Issue 5 , 717 - 725 (2009). Gambaran Lama Hari Rawat Dalam Terjadinya Luka Dekubitus Pada Pasien Immobilisasi di RSUP Haji Adam Malik Medan. Skripsi Fakultas Keperawatan Universitas Sumatera Utara. (2010). Hubungan Tingkat Pengetahuan Dan Sikap Dengan Perilaku Perawat Dalam Upaya Pencegahan Dekubitus Di Rumah Sakit Cakra Husada Klaten, Jurnal KesMaDaSka, Vol 1 No. 1, Juli. Suriadi, Sanada,H., Sugama, J., Thigpen,B., Subuh, M. (2008).Development of a new risk assessment scale for predicting pressure ulcer in an intensive care unit. Journal Compilation British Association of Critical Care Nurses. 13(1), 34-43. Suriadi, Sanada H, Kitagawa A, et.al. (2003). Study of reliability and validity of the braden scale translated into indonesia..Master thesis. Kanazawa University, Japan. Download Full Text PDF >>